Development of retrofit, low-deflection portable concrete barrier system. Issue 4 (4th July 2019) - Bielenberg, Robert W.; Faller, Ronald K.; Reid, John D.; Schmidt, Jennifer D.; Asadollahi Pajouh, Mojdeh; Emerson, Erik
ABSTRACT: A retrofit stiffening mechanism was developed for use in reducing the deflection of an F -shape portable concrete barrier (PCB) system without requiring anchorage of the barrier segments to the road surface. The research effort included development and analysis of mechanisms for limiting deflections through engineering analysis and finite element analysis with LS-DYNA. Deflection-limiting mechanisms investigated included increased barrier mass, increased barrier-to-ground friction, reduction of the joint gap, and composite action. Following analysis of the candidate designs, an initial prototype design was developed based on using composite action to provide moment continuity across the barrier joints. This design was successfully evaluated in full-scale crash tests. Following the first crash test, the low-deflection PCB system was modified to further reduce deflections and full-scale crash tested a second time. The final version of the low-deflection PCB system was capable of reducing dynamic barrier deflections almost 50% over free-standing PCB installations while still safely redirecting errant vehicles.